The management of impacted mandibular third molars with coronectomy procedure: Rapid review - Septiani, Tiara Ika; Yuza, Abel Tasman; Hadikrishna, Indra (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACT Introduction: The extraction of impacted third molar teeth often experiences complications. Post-extraction complications of third molar teeth include pain, dry socket, and inferior alveolar nerve injury. Inferior alveolar nerve injury is a typical complication of extraction of mandibular third molars. Coronectomy is an alternative procedure used to treat impacted third molars. Coronectomy is considered a good procedure in reducing the injury to the inferior alveolar nerve (IAN). The purpose of this study was to determine the advantages and disadvantages of treating impacted mandibular third molars with coronectomy procedures. Methods: In this study, the researchers used a rapid review method that refers to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Electronic search of articles was carried out on three electronic databases, namely the National Library of Medicine (Medline / PubMed), Cochrane Library, and Sciencedirect. Results: Of the 6 articles reviewed, 2 articles assessing the comparison between extraction and coronectomy showed that coronectomy was better in reducing the occurrence of complications. The other 4 articles have no or few case reports of neurological disorders. Other outcomes of coronectomy such as pain, infection, alveolar osteitis was equal or lower than those of complete extraction. The results of root migration after coronectomy were quite high and the results of teeth requiring reoperation were lower, with follow-up periods varying between articles. Conclusion: Coronectomy is indicated if the mandibular third molars are close to the inferior alveolar nerve and coronectomy has been shown to reduce the incidence of IAN and dry socket injuries.KEY WORDS: Coronectomy, impacted third molars, injury inferior alveolar nerve, rapid review.Tatalaksana impaksi gigi molar ketiga mandibula dengan prosedur coronectomy: rapid reviewABSTRAK Pendahuluan: Pencabutan impaksi gigi molar ketiga sering kali mengalami komplikasi. Komplikasi pasca pencabutan gigi molar ketiga diantaranya rasa nyeri, dry socket, dan cedera saraf alveolaris inferior. Cedera saraf alveolaris inferior adalah komplikasi khas dari pencabutan gigi molar ketiga rahang bawah. Coronectomy merupakan salah satu tindakan yang digunakan untuk perawatan impaksi gigi molar ketiga. Coronectomy dianggap sebagai prosedur yang baik dalam mengurangi terjadi cedera pada inferior alveolar nerve (IAN). Tujuan penelitian ini untuk mengetahui keuntungan dan kerugian dari perawatan impaksi gigi molar tiga rahang bawah dengan prosedur coronectomy. Metode: Dalam penelitian ini peneliti menggunakan metode rapid review yang mengacu pada panduan Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Pencarian artikel secara elektronik dilakukan pada tiga basis data elektronik yaitu National Library of Medicine (Medline/Pubmed), Cochrane Library, dan Sciencedirect. Hasil: Dari enam artikel yang ditinjau, dua artikel menilai perbandingan antara odontectomy dan coronectomy menunjukan bahwa coronectomy lebih baik dalam mengurangi terjadinya komplikasi pasca operasi. Empat artikel lainnya menunjukan tidak ada atau sedikit laporan kasus terjadinya cedera saraf. Hasil lain dari coronectomy seperti nyeri, infeksi, osteitis alveolar sama atau lebih rendah dibandingkan dengan odontectomy. Hasil terjadinya migrasi akar setelah tindakan coronectomy cukup tinggi dan hasil dari gigi yang memerlukan operasi ulang lebih rendah, untuk jangka waktu follow-up bervariasi setiap artikelnya. Simpulan: Coronectomy diindikasikan jika gigi molar ketiga mandibula dekat dengan saraf alveolaris inferior dan coronectomy terbukti mengurangi cedera IAN dan dry socket.KATA KUNCI: coronectomy, impaksi gigi molar ketiga, cedera saraf alveolar inferior, rapid review.